Donor-derived Cryptococcus gattii complex infection after liver transplantation - Bruno Hassunuma Carneiro; Giovanni Luis Breda; Regielly Caroline Raimundo Cognialli; Germana Davila dos Santos; Vania Aparecida Vicente; Eduardo Gnoatto Perondi; João Cesar Beenke França; Flávio Queiroz-Telles (Revista da Sociedade Brasileira de Medicina Tropical)
ABSTRACT Cryptococcal disease is the third most common invasive fungal infection in solid organ transplant recipients and is associated with high-morbidity and -mortality rates. Donor-derived Cryptococcus spp. infection typically manifests within the first month post-procedure and has historically been caused by C. neoformans complex, predominantly in kidney recipients, but also after liver transplantation. We report the first documented case of donor-derived, early-onset C. gattii complex meningoencephalitis following liver transplantation in a 54-year-old woman, successfully treated with amphotericin B and fluconazole, and review the relevant literature.